Direct effect of interleukin-6 (IL-6) on growth plate chondrocytes - 今川, 智之; 宮前, 多佳子; 森, 雅亮; 成戸, 卓也; 中島, 章子; 横田, 俊平 (Nihon Rinsho Men'eki Gakkai Sokai Shorokushu, 2007)
Background: Growth impairment is a major complication of systemic juvenile idiopathic arthritis (sJIA). Aims: To investigate the cellular-level effect of IL-6 on the growth plate chondrocytes. Materials and Methods: The murine chondrocyte EC cell line, ATDC5 was examined for the expression of IL-6 receptor and gp130 by fluorescence-activated cell sorting (FACS) analysis. Cells were harvested for 14 full days and recombinant murine IL-6 was added to the cultures from day 2 to day 14. To study the effect of IL-6 on cell differentiation, the quantitative real-time reverse transcriptase polymerase chain reaction (qRT-PCR) was performed for the chondrogenic differentiation markers, type II collagen, aggrecan, and type X collagen. To test IL-6 function blocking, MR16-1, the anti-mouse IL-6 receptor monoclonal antibody, was used. Results: FACS analysis revealed the expression of IL-6 receptor and gp130 on the surface of ATDC5 cells. The results of qRT-PCR indicated that IL-6 reduced the expressions of chondrogenic differentiation marker gene. A blocking test showed that the inhibitory effect of IL-6 was abrogated. Conclusion: The results indicate that IL-6 inhibits the early differentiation of growth plate chondrocytes at a cellular level. Growth impairment in sJIA is brought about in part through the direct inhibitory effect of IL-6 on early differentiation of growth plate chondrocytes.